Pravostranná hemikolektomie a kompletní mesokolická excize - naše zkušenosti - Adamová, Zuzana; Slováček, Radim; Weberová, B (Miniinvazívna chirurgia a endoskopia, chirurgia súčasnosti, 2021)
Objective Laparoscopic complete removal of mesocolon (complete mesocolic excision, CME) with central vascular ligation (CVL) in the surgical management of right sided colonic cancer is a novel technique. Our aim was to evaluate number of lymph nodes and short term outcome when compared to less radical laparoscopic surgery. Methods Data were collected in 56 right sided colon cancer patients operated on between 2016 and 2019. Patients were divided into two groups, including those undergoing surgery before (32) or after (24) December 2017 when CME was introduced in our hospital. Results The mean number of harvested lymph nodes increased from 17 to 25 (p=0.003). The mean operation time was longer in CME group 168 versus 148 min (p=0.007). Morbidity did not differ in both groups significantly, just surgical site infections were lower in CME group (0 versus 19% (p=0.02). The median length of hospital stay increased from 8 to 8,5 days,t the difference is not statistically significant. Conclusion Complete mesocolic excision is associated with greater lymph node yield but longer operating time, acceptable morbidity and length of hospital stay.
Keywords: nádory tračníku; lymfatické uzliny; Aged; Aged, 80 and over; Laparoscopy; Retrospective Studies; lidé středního věku; senioři; Colectomy; lidé; Lymph Nodes; Adult; Middle Aged; mezokolon; dospělí; Female; senioři nad 80 let; Male; ženské pohlaví; Mesocolon; laparoskopie; Humans; mužské pohlaví; kolektomie; Colonic Neoplasms; retrospektivní studie